Automated Support for the Design and Validation of Fault Tolerant Parameterized Systems: a case study - Alberti, Francesco; Ghilardi, Silvio; Pagani, Elena; Ranise, Silvio; Rossi, Gian (Electronic Communications of the EASST, 2011)
We propose a methodology to use the infinite state model checker MCMT, based on Satisfiability Modulo Theory techniques, for assisting in the design of fault tolerant algorithms. To prove the practical viability of our methodology, we apply it to formally check the agreement property of the reliable broadcast protocols of Chandra and Toueg.